2017
DOI: 10.1039/c7nj00441a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of mesoporous silica with different pore sizes for cellulase immobilization: pure physical adsorption

Abstract: The microstructure of mesoporous silica and their adsorbing cellulase process have been analyzed to investigating the physical adsorption mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 41 publications
0
25
0
2
Order By: Relevance
“…The adsorbed amount increased from 25 to 50 °C according to an Arrhenius-like trend. This indicates that the adsorption of cellulase on WSNs in endothermic in nature [ 12 , 34 ]. Adsorption at higher temperatures has not been analysed because enzymes are normally prone to thermal deactivation by denaturation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The adsorbed amount increased from 25 to 50 °C according to an Arrhenius-like trend. This indicates that the adsorption of cellulase on WSNs in endothermic in nature [ 12 , 34 ]. Adsorption at higher temperatures has not been analysed because enzymes are normally prone to thermal deactivation by denaturation.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Zhang et al [ 35 ] covalently immobilized cellulase on silica gel substrate, retaining only 7% of its specific activity in the hydrolysis of CMC. Chen et al [ 12 ] immobilized cellulase on mesoporous silica with different pore size, obtaining at the best a retention of 63.3% of free cellulase activity. Takimoto et al [ 11 ] immobilized cellulase in SBA-15 with different pore size: the best biocatalyst preserved 67.5% of the activity of the free form.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in the apparent K M upon immobilization suggested mass transfer limitations, due to both the sticking of the nanoparticles and a crowding effect due to the excessive amount of enzyme inside the pores. The decrease in V max may be ascribed to detrimental modifications in the enzyme conformation for the bridging enzymes [50] and a loss of the conformational flexibility caused by interactions between the polypeptide molecules and with the matrix [58]. Concerning the immobilization of BG on nanoparticle carriers, Verma et al [27] immobilized a thermostable enzyme (β-glucosidase from Aspergillus niger) on functionalized magnetic nanoparticles by covalent binding.…”
Section: Resultsmentioning
confidence: 99%
“…Later, Chen et al found the similar result by using a mesoporous silica materials as the support for immobilizing cellulase. [ 24 ] The mesoporous silica with a pore size of 3.8 nm exhibited the best activity, which just matched the short axes of cellulase molecules. Washmon‐Kriel et al fabricated a novel hierarchical magnetic mesoporous silica microspheres with different pore sizes and open pore structures through a water/oil biphase synthetic strategy.…”
Section: Enzymatic Biosensorsmentioning
confidence: 98%